Neutrophils in malaria: A double-edged sword role - Babatunde, Kehinde Adebayo; Adenuga, Oluwadamilola Fatimat (Frontiers in Immunology, 2022)
ABSTRACT Neutrophils are the most abundant leukocytes in human peripheral blood. They form the first line of defense against invading foreign pathogens and might play a crucial role in malaria. According to World Health Organization (WHO), malaria is a globally significant disease caused by protozoan parasites from the Plasmodium genus, and it’s responsible for 627,000 deaths in 2020. Neutrophils participate in the defense response against the malaria parasite via phagocytosis and reactive oxygen species (ROS) production. Neutrophils might also be involved in the pathogenesis of malaria by the release of toxic granules and the release of neutrophil extracellular traps (NETs). Intriguingly, malaria parasites inhibit the anti-microbial function of neutrophils, thus making malaria patients more susceptible to secondary opportunistic Salmonella infections. In this review, we will provide a summary of the role of neutrophils during malaria infection, some contradicting mouse model neutrophil data, and neutrophil-related mechanisms involved in malaria patients’ susceptibility to bacterial infection. Keywords: Neutrophil, malaria, Plasmodium, NETs, and Salmonella typhimurium.